2022
DOI: 10.3390/su14137822
|View full text |Cite
|
Sign up to set email alerts
|

Historic Churches and Their Hygrothermal Environment: A Review of Criteria Related to Building Fabric, Artefacts, Artwork and Occupants

Abstract: Regarded as important cultural heritage, historic churches have been utilised over hundreds of years for worship and community benefit. Simple on/off space heating systems are installed in many churches to increase human comfort. However, the conservation of the important historic artefacts and artwork contained within may not have been fully considered. This review attempts to appraise the standards in place for artefacts and artwork. A consensus of 15–25 °C and 40–65% relative humidity is established as safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…It was found that the deterioration and mold problems of ancient buildings are influenced by the coupling of multiple factors, such as the thermal and humid environment around the building, air flow, underground soil moisture, and the building envelope, etc. [8][9][10]. Exploring the patterns of influence of different factors on the deterioration of ancient buildings is an important prerequisite for taking effective conservation measures.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the deterioration and mold problems of ancient buildings are influenced by the coupling of multiple factors, such as the thermal and humid environment around the building, air flow, underground soil moisture, and the building envelope, etc. [8][9][10]. Exploring the patterns of influence of different factors on the deterioration of ancient buildings is an important prerequisite for taking effective conservation measures.…”
Section: Introductionmentioning
confidence: 99%
“…In Huijbregts et al [97], the authors use a HAMBase model (heat, air, and moisture model for building and system evaluation) combined with a FEM software to assess the risk of mechanical degradation of a wooden cabinet after a new heating system was installed. When the artefacts are housed in a historic building, a heating, ventilation, and air conditioning (HVAC) system is usually installed to avoid uneven temperature and relative humidity fluctuations; this environment is often influenced by the outdoor environment [110][111][112]. Through the described approach, which combines the building simulation and the moisture transport at the material level, it is possible to directly simulate the impact of the HVAC system on the moisture-related mechanical stress [95].…”
Section: Mathematical Modelling and Numerical Simulationsmentioning
confidence: 99%